(untitled) (SALAM Digest: Syariah and Law Undergraduate Symposium, 2023)
Genetically modified food (GMF) is one of the advances in biotechnology that has become a contentious issue with strong arguments on both sides. Proponents of GMF highlight its potential benefits, such as increased food production, improved nutritional value, and enhanced crop resistance, while opponents’ express concerns about potential health and environmental risks, along with ethical and socioeconomic implications. Therefore, the Muslim community becomes doubtful whether it is allowed in Islam or not. A detailed qualitative approach based on library research was used to explore those issues, and all data were descriptively examined. Through this research, every genetically modified food product must meet the principles of maqasid syariah while also benefiting human life, health, and finance without neglecting the concept of halalan tayyiban (permitted and clean) and not harming people. It also addresses the Malaysian regulatory framework for ensuring GMF safety for Muslim consumers.